Advanced rheological characterization of Reacted and Activated Rubber (RAR) modified asphalt binders. (30th September 2016) - Kedarisetty, Sampat; Biligiri, Krishna Prapoorna; Sousa, Jorge B.
Highlights: Performed advanced rheological characterization of 10 RAR modified binders at different temperature-frequency combinations. Found significant reduction in viscosity-temperature susceptibility and strain responses with RAR modification. Noticed augmentation of Performance Grade temperatures due to RAR inclusions in asphalt. Established minimal dosage of RAR to improve asphalt binder rheological properties. RAR is a promising additive to enhance asphalt binder performance characteristics. Abstract: The objective of this research study was to conduct binder characterization of the Reacted and Activated Rubber (RAR) modified asphalts with varying dosages, and compare these materials with two virgin and one commercially available rubber modified (C60) binders. RAR modification raised the upper Performance Grade temperatures to a higher grade than the base binder making these binders well suited to reduce rutting. Non-recoverable creep compliance decreased and recovery increased with increasing RAR contents. RAR modified asphalts were highly resilient in nature since they had substantially lower strains than the virgin and C60 binders attributed to the presence of RAR additive that provided it an enduring viscoelastic characteristic. Overall, it is recommended that at least 15% RAR be used as minimal dosage in designing an asphalt mixture to obtain an effective material with an improved performance than a mixture produced using commercially available asphalts, including the rubber-modified ones.